Ecological traits influencing range expansion across large oceanic dispersal barriers: insights from tropical Atlantic reef fishes - Luiz, Osmar J; Madin, Joshua S; Robertson, D Ross; Rocha, Luiz A; Wirtz, Peter; Floeter, Sergio R (Proceedings of the Royal Society. B, Biological sciences, 2012)
How do biogeographically different provinces arise in response to oceanic barriers to dispersal? Here, we analyse how traits related to the pelagic dispersal and adult biology of 985 tropical reef fish species correlate with their establishing populations on both sides of two Atlantic marine barriers: the Mid-Atlantic Barrier (MAB) and the Amazon-Orinoco Plume (AOP). Generalized linear mixed-effects models indicate that predictors for successful barrier crossing are the ability to raft with flotsam for the deep-water MAB, non-reef habitat usage for the freshwater and sediment-rich AOP, and large adult-size and large latitudinal-range for both barriers. Variation in larval-development mode, often thought to be broadly related to larval-dispersal potential, is not a significant predictor in either case. Many more species of greater taxonomic diversity cross the AOP than the MAB. Rafters readily cross both barriers but represent a much smaller proportion of AOP crossers than MAB crossers. Successful establishment after crossing both barriers may be facilitated by broad environmental tolerance associated with large body size and wide latitudinal-range. These results highlight the need to look beyond larval-dispersal potential and assess adult-biology traits when assessing determinants of successful movements across marine barriers.